265 Phase 1b study of avelumab + M9241 (NHS-IL12) in patients with advanced solid tumors: interim analysis results from a urothelial carcinoma (UC) dose-expansion cohort. (9th November 2020) - Deville, Jean-Laurent; Ravaud, Alain; Maruzzo, Marco; Gourdin, Theodore; Maio, Michele; Dirix, Luc; Wang, XiaoZhe; Vugmeyster, Yulia; Beier, Frank; Seebeck, Jeorg; Chennoufi, Sarah; Gulley, James
Abstract : Background: Avelumab is an anti–PD-L1 monoclonal antibody approved for the treatment of advanced UC after disease progression during or following platinum-based chemotherapy and as maintenance treatment in patients whose disease has not progressed with first-line platinum-based chemotherapy. 1–3 M9241 is an immunocytokine composed of 2 heterodimers of IL-12 fused to the heavy chains of a human antibody targeting DNA released from necrotic tumor cells. 4 During dose-escalation, avelumab + M9241 was well tolerated and showed promising antitumor activity in patients with advanced solid tumors, including 2 objective responses in patients with UC. 5 We report on an interim analysis of efficacy and safety from the dose-expansion part of JAVELIN IL-12 (NCT02994953 ). Methods: Eligible patients had locally advanced or metastatic UC that had progressed on first-line therapy, were aged =18 years, had an Eastern Cooperative Oncology Group performance status of 0/1, and were immune checkpoint inhibitor naive. Patients received the recommended phase 2 dose 5 of avelumab 800 mg intravenously once weekly (QW) in combination with M9241 16.8 µg/kg subcutaneously Q4W for the first 12 weeks, then continued the combination with avelumab Q2W. The primary endpoints were confirmed best overall response (BOR) per investigator assessment (RECIST 1.1) and safety. The expansion cohort followed a 2-stage design. During stage 1 (single-arm part of the study), 16 patients were enrolled and treated. A futility analysis based on BOR was planned to determine if stage 2 (randomized controlled part of the study) would be initiated. Results: At data cut-off (Jun 3, 2020), 16 patients had received avelumab + M9241 for a median duration of 8 weeks (range, 4.0–25.0 weeks). No complete or partial responses were observed; the study failed to meet the criterion (>2 responders) to initiate stage 2. Two patients (12.5%) had stable disease, 13 (81.3%) had progressive disease, and 1 (6.3%) was not evaluable. Any-grade treatment-related adverse events (TRAEs) occurred in 15 patients (93.8%); the most common (in =4 patients) were pyrexia (50.0%), nausea (37.5%), asthenia (31.3%), anemia (25.0%), and hyperthermia (25.0%); grade 4 gamma-glutamyltransferase increased occurred in 1 patient (6.3%). No TRAEs led to death. Pharmacodynamic effects on the peripheral immune system and results of pharmacokinetic and biomarker analyses will also be reported. Conclusions: The predefined efficacy criterion to proceed to stage 2 was not met. The combination was well tolerated; no new safety signals emerged and the profile was consistent with the dose-escalation part of the study. 5 Trial Registration: NCT02994953 Ethics Approval: The study was approved by each site's independent ethics committee. Consent: N/A References: Bavencio(avelumab) injection [package insert]. Rockland, MA: EMD Serono, Inc; New York, NY: Pfizer Inc; 2020. Health Canada. https://www.canada.ca/en/health-canada.html. Accessed July 31, 2020. US Food and Drug Administration. FDA approves avelumab for urothelial carcinoma maintenance treatment. https://www.fda.gov/drugs/drug-approvals-and-databases/fda-approves-avelumab-urothelial-carcinoma-maintenance-treatment. Accessed July 31, 2020. Fallon J, Tighe R, Kradjian G, et al. The immunocytokine NHS-IL12 as a potential cancer therapeutic. Oncotarget . 2014;5 :1869–1884. Strauss J, Vugmeyster Y, Sznol M, et al. Phase 1b, open-label, dose escalation study of M9241 (NHS-IL12) plus avelumab in patients (pts) with advanced solid tumours. Ann Oncol . 2019;30(5 Suppl):Abstract 4062.